THE INFLUENCE OF FINANCIAL LITERACY ON FINANCIAL BEHAVIOR WITH FINANCIAL RISK TOLERANCE AS A MEDIATOR AND EMOTIONAL INTELLIGENCE AS A MODERATOR IN GEN Z OF CENTRAL JAVA PROVINCE - Linda Susilowati; Dwi Cahyaningdyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to examine the effect of financial literacy on financial behaviour among Generation Z in Central Java, Indonesia, by investigating the mediating role of financial risk tolerance and the moderating role of emotional intelligence. This study employed a quantitative approach using a survey method. Data were collected through a structured questionnaire distributed to Generation Z respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that financial literacy positively and significantly influences financial behaviour (β = 0.487, p < 0.001) and financial risk tolerance (β = 0.587, p < 0.001). Financial risk tolerance also positively affects financial behaviour (β = 0.342, p < 0.001). Emotional intelligence positively influences financial risk tolerance (β = 0.315, p = 0.001), but it does not directly influence financial behaviour (β = -0.024, p = 0.715). Furthermore, emotional intelligence strengthens the influence of financial literacy on both financial behaviour and financial risk tolerance. Financial risk tolerance also mediates the relationships between financial literacy and financial behaviour, as well as between emotional intelligence and financial behaviour. This study contributes to the literature by proposing a moderated mediation model that integrates cognitive, emotional, and risk management dimensions to explain sustainable financial behaviour among Generation Z in the digital economy.